2013
DOI: 10.1016/j.fuproc.2012.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of burning velocities of ultra-wet methane–air–steam mixtures

Abstract: Global burning velocities of methane-air-steam mixtures are measured on prismatic laminar Bunsen flames and lifted turbulent V-flames for various preheating temperatures, equivalence ratios and steam mixture fractions at atmospheric pressure. Experiments are conducted on a new rectangular slot-burner. Experimental burning velocities are compared to computed flame speeds of one dimensional adiabatic premixed flames using detailed mechanisms (Konnov 0.5 and GRI Mech 3.0). Mean profiles of radicals OH * are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Table 1 gives an overview of the investigated combustor operating conditions. The inlet temperature T in as well as the adiabatic flame temperature T ad were calculated using CANTERA and the GRI 3.0 mechanism (Smith et al, 2000), which was shown to reasonably perform even at high steam-dilution rates (Albin et al, 2013). Subsequently, the temperature of the burnt gases T fl was estimated using an empirical correlation .…”
Section: Combustion Test Rigmentioning
confidence: 99%
“…Table 1 gives an overview of the investigated combustor operating conditions. The inlet temperature T in as well as the adiabatic flame temperature T ad were calculated using CANTERA and the GRI 3.0 mechanism (Smith et al, 2000), which was shown to reasonably perform even at high steam-dilution rates (Albin et al, 2013). Subsequently, the temperature of the burnt gases T fl was estimated using an empirical correlation .…”
Section: Combustion Test Rigmentioning
confidence: 99%
“…There have been a number of studies on the impact of H 2 O on the burning velocity of CH 4 [22][23][24][25]. While all three tested mechanisms can predict the decrease of the burning velocity through H 2 O addition equally well at atmospheric pressure, AramcoMech 1.3 performs better at elevated pressure (see Fig.…”
Section: Mechanism For Oxy-fuel Combustion Of Chmentioning
confidence: 97%
“…Stratified charge engines and large gas engines use lean combustion to achieve these objectives [2,3], resulting in longer combustion durations and lower power density of the engine. To avoid efficiency losses, the grade of turbulence and the boost pressure can be increased [4]. These measures increase the demands for the ignition system [5].…”
Section: Introductionmentioning
confidence: 99%